Skin/Muscle Incision and Retraction Induces Evoked and Spontaneous Pain in Mice - Yang, Juan (Pain Res Manag, 2019)
BACKGROUND: Surgery is a frequent cause of persistent pain. Unrelieved chronic postsurgical pain causes unnecessary patient suffering and discomfort and usually leads to psychological complications. The rat model of skin/muscle incision and retraction (SMIR) with decreased paw withdrawal thresholds developed by Flatters was usually used to investigate the underlying mechanism of chronic postsurgical pain. OBJECTIVES: The aim of our study was to develop a new mice model of SMIR for further investigation with transgenic mice and so on and to evaluate the analgesic effects of clonidine and gabapentin on pain behavior with this new mice model. METHODS: Male C57BL/6 mice were anesthetized, and a 1.0–1.3 cm incision was made in the skin of the medial thigh approximately 3 mm medial to the saphenous vein to reveal the muscle of the thigh. The paw withdrawal threshold (PWT) to mechanical stimuli and the paw withdrawal latency to heat stimuli were measured before and after SMIR. Furthermore, the PWT to mechanical stimuli and conditioned place preference (CPP) was measured before and after the systemic injection of clonidine and gabapentin. RESULTS: SMIR-evoked mechanical hypersensitivity in mice began on day 1 after the procedure, prominent between days 1 and 10 after the procedure, persisted at least until day 14, and disappeared on day 18 after the procedure. However, the mice model of SMIR did not evoke significant heat hypersensitivity. Systemic injection of clonidine and gabapentin raised the PWT in the SMIR mice dose-dependently. Compared with the mice that underwent the sham operation, mice of SMIR spent a longer time in the clonidine-paired chamber than those of NS, while the gabapentin-paired chamber has no difference with that of NS in the CPP paradigm. CONCLUSION: These data suggested that the mice model of SMIR demonstrated a persistent pain syndrome, including evoked pain and spontaneous pain. Clonidine and gabapentin could relieve mechanical hypersensitivity dose-dependently simultaneously. However, clonidine but not gabapentin could alleviate the spontaneous pain of SMIR in the mice model.